The response of competitors to announcements of bankruptcy: An empirical examination of contagion and competitive effects - Ferris, Stephen P.; Jayaraman, Narayanan; Makhija, Anil K. (Journal of Corporate Finance, 1997)
We find, like [Lang, L.H.P., Stulz, R.M., 1992. Contagion and competitive intra-industry effects of bankruptcy announcements: An empirical analysis, Journal of Financial Economics, 32(1), 45–60], that large firm bankruptcies generate a dominant contagion effect. A value-weighted portfolio of competitors' stocks experiences a significant loss of 0.56% in the three days centered around the Chapter 11 announcement. This represents an average loss of $3.32 for all the competitors combined for every dollar lost by the bankrupt firm. In addition, we find that small firm bankruptcies also generate a dominant contagion effect among smaller sized competitors; an equally-weighted portfolio of all competitors has a significant 0.12% drop. In a new approach to separate the contagion and competitive effects, we compare the stock price reactions of competitors who themselves subsequently file for bankruptcy in the next three years (candidates for contagion effect) with those who do not do so (candidates for competitive effect). As expected, candidates for contagion effect experience a significant, negative three-day stock price reaction of −4.68%. However, contrary to expectations, candidates for competitive effect also have a significant, negative return (−0.49%), suggesting that the competitive effect is weak at best since it is dominated by the contagion effect even in this sample. Other procedures to identify candidates for competitive effect generally yield similar findings. Finally, we analyze competitors' stock price reactions based on selected characteristics (e.g., industry concentration, and leverage), with similar results as before. One explanation for the failure to detect a competitive effect is that the impact may already have been incorporated in stock prices prior to the filing for Chapter 11. Consistent with this explanation, we find significant positive stock price reactions by competitor stocks for the hundred days prior to the bankruptcy announcement.